Household resources and practices toward native rice sufficiency in Khoune district, Xiengkhouang province, Lao PDR - Chanthavongsa, Kolakanh; Dizon, Josefina T.; Amit, Mayo Grace C.; Quimbo, Maria Ana T. (2015)
A case study was conducted in Na-OU and Xang villages in Khoune district, Xiengkhouang province, Lao PDR to discuss the households' resources and practices in attaining native rice sufficiency. Data were gathered through a combination of methods that included a survey of 91 households, focus group discussions, key informant interviews, actual field observations, and secondary data analysis. The study villagers are largely rural, popular nationwide for their native sticky rice varieties, and regarded as models in native sticky rice production. There are also areas of wetland for rice cultivation that are suited to grow the age-old native sticky rice varieties.

The native rice farmers in these villagers are rice self-sufficient because of their household resources and practices. In their households, they possess adequate farming experiences, land parcels, household technology, farm tools, basic farm machinery, organic fertilizers, rice storage system, and positive attitude and unwavering intent to crop their age-old sticky rice varieties. Their household level practices that contribute to their native rice sufficiency are use of technology that is fundamentally traditional and suitable to the place; engaging in husband-wife enterprise; familial and communal rice farming; and seed variety preservation.
Keywords: Laos--Rice farming; Rice production